VISCERAL FAT INDEX INFORMS RISK OF MEDICALLY REFRACTORY IBD AND NEED FOR SURGERY IN PATIENTS STARTING ANTI-TUMOR NECROSIS FACTOR (TNF) THERAPY. (21st January 2021) - Gu, Phillip; Chhabra, Avneesh; Chhittajallu, Punya; Chang, Christopher; Mendez, Denisse; Gilman, Andrew; Fudman, David; Xi, Yin; Feagins, Linda
Abstract: Background: Increased visceral adipose tissue (VAT) is associated with systemic inflammation through amplified production of pro-inflammatory cytokines like TNF-α and interleukin-6. Higher visceral fat index (VFI), which is the ratio of VAT to subcutaneous adipose tissue (SAT) and reflects the degree of excess VAT in relation to SAT, is associated with complex IBD. However, its relevance to treatment response is unclear. We aim to evaluate the effect of VFI on treatment response and risk of surgery in IBD patients starting anti-TNF therapy. Methods: IBD patients starting anti-TNF agents between 1/1/2009 to 7/31/2019 at two academic medical centers were included. Three dimensional VAT and SAT volumes were measured from CT scans with Aquarius (iNtuition, Foster City, CA). VFI was calculated with the ratio of VAT:SAT. Patients were categorized by predefined VFI cutoffs: <0.33, 0.33–0.66, > 0.67. Primary outcomes included composite endpoint of corticosteroid-free response (CFR) at 6 and 12 months defined by meeting one of the following: a) clinical response based on Harvey Bradshaw Index for Crohn's disease (CD) or Lichtiger score for ulcerative colitis (UC), b) endoscopic improvement based on ulcer healing for CD and Mayo score for UC compared to baseline, or c) 50% improvement or normalization of CRP or fecal calprotectin. Secondary outcomes included IBD-related surgery at 6 and 12 months. We performed a multivariable logistic regression on CFR and surgery, adjusting for age, gender, IBD diagnosis, disease duration, active tobacco use, and immunomodulator exposure, to calculate adjusted odds ratio (aOR) and 95% confidence interval (CI). Results: We included 181 patients. Table 1 summarizes differences in baseline characteristics. There were no differences in disease severity or activity. There were no differences in CFR at 6 and 12 months (Figure 1a and b ). With respect to surgery within 6 months, patients with VFI > 0.67 were significantly more likely to undergo surgery (aOR: 41.92 [95%CI 5.09–345.59]), but no difference in patients with VFI 0.33–0.66 was observed when compared to patients with VFI <0.33 (aOR: 2.23 [95%CI 0.48–11.21]). Similarly at 12 months, patients with VFI > 0.67 were more likely to undergo surgery (aOR: 15.55 [95%CI 2.85–80.56]) but no difference was observed in patients with VFI 0.33–0.66 compared to patients with VFI <0.33 (aOR: 1.38 [95%CI 0.36–5.29]). Conclusion: In this retrospective, multicenter, cohort study, we found higher VFI is associated with increased odds of surgery in IBD patients starting anti-TNF therapy. If confirmed by future prospective studies, VFI may be employed as a biomarker to help identify IBD patients at risk for medically refractory disease and would benefit from an early surgical referral, especially considering the growing application of artificial intelligence in medical imaging.